Article Review: The Role of Botany in Forensic Investigations - Abid, Istiana Firqah; Afdhila, Zakia (LPPM Universitas Muhammadiyah Riau, 2025)
Botany is the study of plants and plant life. Forensic botany is the study of plants, their relation to law and legal issues and can be used as evidence in a case. The characteristics and parts of each plant can be used as evidence when found on the body or things related to a person or the scene of a case. Botanical evidence found at a crime scene can be used to assist the investigation process related to the relationship between the victim, the perpetrator and the scene. The evidence found can be evidence that can be seen directly and microscopic evidence that requires laboratory analysis for identification, therefore forensic botanical analysis must be carried out by experts in the field of botany. Forensic botanical evidence in an investigation can provide information related to the estimated time of death, how long the victim was buried, the cause and manner of death.